A new quench detection method for HTS magnets: stray-capacitance change monitoring. (4th December 2019) - Ravaioli, E; Davis, D; Marchevsky, M; Sabbi, GL; Shen, T; Verweij, A; Zhang, K
Abstract: Fast quench detection is a key requirement for the successful implementation of superconducting magnet technology. In high temperature superconductor magnets, this issue is especially challenging due to the low quench propagation velocity, and presently represents one of the main factors limiting their application. A new detection technique based on stray-capacitance monitoring is proposed. The capacitance between electrically-insulated magnet elements, such as magnet structure and end parts, is utilized as an indication of local heat deposition in the conductor. In fact, the relative permittivity of helium drops when it changes from the liquid to the gaseous phase. Thus, when heating occurs, part of the helium impregnating the insulation layers boils off, and the monitored stray-capacitance decreases. The proposed technique is successfully demonstrated on three small-scale Bi-2212 magnets manufactured at the Lawrence Berkeley National Laboratory. Results from the detection of thermal runaways and spot-heater induced quenches are reported and discussed. Advantages and limitations of the stray-capacitance method with respect to conventional quench detection methods are assessed.